Dr. Mahathir Mohammad a wise man in a crazy world - Abdulrahim Abdulwahid (Media Hub Connection Sdn. Bhd., 2016)
A newer version, thus, is due to exhibit Mahathir's glorious vison, both locally and internationally, from 2003 to 2014. This latest version will hopefully cober the recent events, including the Arab Spring, the Syrian crisis, Palestinian crisis and more issues.